The effect of post-mastectomy radiation in women with one to three positive nodes enrolled on the control arm of BCIRG-005 at ten year follow-up. Issue 1 (April 2017) - Tam, Moses M.; Wu, S. Peter; Perez, Carmen; Gerber, Naamit Kurshan
Abstract: Background and purpose: We evaluated the effect of post-mastectomy radiation (PMRT) in 1–3 positive lymph nodes (LN) in patients who received uniform modern systemic therapy. Materials and methods: Cohort study using individual data collected for 1, 649 node-positive women who received doxorubicin/cyclophosphamide with sequential docetaxel in 2000–2003 on the control arm of BCIRG-005. All women underwent mastectomy or lumpectomy and axillary LN dissection. PMRT was given at investigator's discretion. Results: A total of 523 women with 1–3 positive LN underwent mastectomy and 39% (206/523) received PMRT. With a median follow-up of 10 years, PMRT improved loco-regional control (LRC) from 91% to 98% ( p = 0.001) but had no effect on overall survival (OS) (84% vs. 86%, p = 0.9). On multivariate analysis, PMRT improved local control (LC) (hazard ratio, 0.14; 95% CI, 0.03–0.62; p = 0.01) and LRC (hazard ratio, 0.15; 95% CI, 0.04–0.50; p = 0.002). PMRT did not significantly impact OS on multivariate analysis (hazard ratio, 0.91; 95% CI, 0.55–1.51; p = 0.7). Results remained consistent with the use of propensity score analysis. Conclusions: In this cohort of patients with N1 disease treated with modern systemic therapy, PMRT improves LRC but has no effect on OS. The rates of OS were excellent, irrespective of adjuvant radiation.